Optimalisasi Performa Sprint: Tinjauan Biomekanika dan Fisiologis - Fatoni Fatoni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the relationship between biomechanical and physiological variables on sprint performance in short-distance runners. A total of 20 male athletes aged 18–21 years were the subjects. Biomechanical data were obtained through video analysis of sprint movements, including stride length, stride frequency, joint angles, and foot contact time. While physiological aspects were measured through vertical jump tests and Running-Based Anaerobic Sprint Test (RAST). Sprint times at distances of 30 and 60 meters were used as performance indicators. The results showed a significant correlation between stride length, foot contact time, cold muscle strength, and anaerobic capacity with sprint time (p <0.05). A negative correlation was found in stride length and muscle strength, while foot contact time showed a positive correlation. These findings confirm that sprint efficiency is greatly influenced by a combination of good biomechanical techniques and optimal physiological capacity. The conclusion of this study is that the development of an effective sprint training program must include an integrated approach between movement technique training and physical condition, to optimize running performance to the maximum.